Local Wisdom as the Foundation for Sustainable Village Development: A Socio-Ecological Analysis of Arborek, Panglipuran, and Ciptagelar Villages - Andika Nur Hardianto; Rita Prihatini; Sabina Ratnawati; Taufik Mei Mulyana; Harafik; Wahyu Agustianto (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Sustainable village development in Indonesia cannot be separated from the role of local wisdom as a social–ecological system that regulates the relationships between humans, the environment, and economic activities. This study aims to analyze the role of local wisdom in natural resource governance, particularly customary forests and their supporting ecosystems, in Kampung Arborek in Raja Ampat, Desa Panglipuran in Bali, and Kasepuhan Ciptagelar in West Java. This research employs a qualitative approach using a literature review method of relevant scientific articles, undergraduate theses, and academic journals. Data analysis is conducted through the perspectives of structural functionalism and symbolic theory to understand the social functions and cultural meanings of local wisdom within each community. The findings indicate that local wisdom serves as the primary foundation of social–ecological governance in all three villages. In Kampung Arborek, customary norms governing the use of marine and coastal resources function as mechanisms for ecosystem conservation and adaptation to tourism development. In Desa Panglipuran, customary regulations manage spatial planning, environmental management, and tourism activities, thereby preserving both cultural and ecological sustainability. Meanwhile, in Kasepuhan Ciptagelar, customary systems regulate the management of customary forests and traditional agriculture, contributing to food security and environmental conservation. Symbolically, local wisdom in these three communities shapes collective identity and environmental ethics by internalizing conservation values in everyday life. This study confirms that local wisdom is a strategic element in sustainable village development that is adaptive to modernization and external pressures.